Bioethics Education: Integrative Sense and Bioethical Sensibility - Todorovska, Marija (Faculty of Philosophy, Skopje, 2017)
When reflected upon, the rapid advancements of bio-medicine, natural sciences and technology are associated with an awareness about the implications of their progress and the possible dangers they carry. А much needed multidisciplinary, pluri-perspective approach of multi-dimensional thinking flourishes in the efforts of integrative bioethics, a self-reflective discipline which serves as an orientation background, offering an integration of perspectives. Bioethical sensibility is a life-long developing ability to be aware of the importance of life, the living (bios), and to acknowledge and tackle issues of bioethics. Bioethics education, although it is still in a somewhat confused state, in a stricter sense focuses on providing appropriate profiles and members of bio-medical professions, science, industry and law with key concepts and references, preparing them for the problems they are going to be facing in dealing with matters of life, and in a broader, more metaphysical sense, continuously encourages bioethical sensibility, in order to build morally excellent characters, deeply concerned about the state of forms and problems of life, not just in individual professional settings, but on all levels connected with the living, the care for otherness, and the planning of a safe and prosperous future. The text examines the points of integrative bioethics and the importance of the nurturing of bioethical sensibility through a comprehensive bioethics education; combines Potter’s idea of bioethics as a bridge to the future with Vuk-Pavlović’s idea of education as actualised (in the) future; shows how character education is fundamental in shaping and developing sensibility for the living; and briefly examines Jahr’s bio-centric approach in bioethics education.
Keywords: bioethics education, integrative bioethics, bioethical sensibility, bio-medicine, character